STUDENTS ARGUMENTATION IN SCIENCE LESSONS: A STORY OF TWO RESEARCH PROJECTS (Jurnal Pendidikan IPA Indonesia, 2016)
The study analysed profiles of students’ argumentation and how lessons may develop students’ argumentation skills. The study was conducted at two Indonesian progressive private schools and a school located in Australian low socio-economic community. This study explored possibilities to draw together results from two different research approaches typical to each country. The Indonesian research project used paper and pencil tests and interviews to investigate students’ argumentation skills, while the Australian research project analysed videos of the lessons. The Indonesian study finds that there is no significant different between two types of schools and gender. The Australian classroom showed shifts in creative dispositions that include the argumentation processes but not a consistent pattern between classes. The Australian teachers actively required students to make claims, explore the robustness of these claims, transferred these claims to new settings and to think of alternative explanations that encouraged students to construct more coherent arguments. This study finds that interpreting and re-interpreting two different research approaches can produce insights that benefit both sides as it can account for the context and needs of each country. In addition, combining of two different methodologies provided perspectives often not collected through single methodologies.